2020
DOI: 10.1111/hae.14200
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and immunological parameters in haemophilia and rheumatoid arthritis patients: a comparative multiplexing laboratory study

Abstract: Introduction Haemophilia (HA) and rheumatoid arthritis (RA) patients may develop joint damage caused by recurrent joint bleedings in HA or by chronic inflammation in RA. Only few data exist for biomarker studies in these patients. Aim The objective of the present study is to assess a large array of biomarkers in peripheral blood samples obtained from HA patients without or with arthropathy and to compare pattern to RA patients and healthy controls. Methods A panel of biomarkers was assessed in 129 men (40 HA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
7
0
1
Order By: Relevance
“…Studies comparing hemophilia patients and control patients showed both increased and decreased levels of cartilage, bone and synovial inflammation markers [7,8,10,11,[19][20][21]. These discrepancies were also noticed in our initial systematic review.…”
Section: Diagnosticsupporting
confidence: 46%
“…Studies comparing hemophilia patients and control patients showed both increased and decreased levels of cartilage, bone and synovial inflammation markers [7,8,10,11,[19][20][21]. These discrepancies were also noticed in our initial systematic review.…”
Section: Diagnosticsupporting
confidence: 46%
“…A recent study by Toenges et al. also showed evidence of systemic inflammation in haemophilia patients with significantly elevated levels of interleukin‐7, ‐10 and ‐12 and other acute phase reactants 3 …”
Section: Introductionmentioning
confidence: 90%
“…2 A recent study by Toenges et al also showed evidence of systemic inflammation in haemophilia patients with significantly elevated levels of interleukin-7, -10 and -12 and other acute phase reactants. 3 Myocardial infarction occurs due to stenosis caused by an atherosclerotic plaque or thrombus formation after plaque rupture. It is in discussion whether the lifelong hypocoagulability in haemophilia patients has protective effects against atherosclerosis and thrombus formation.…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilic arthropathy due to repeated bleeds into the articular cavity is a major cause of morbidity in patients with haemophilia 1 . While the early phase of haemophilic arthropathy has few similarities with rheumatoid arthritis (RA), such as hyperplasia of the synovium lining, the later stages have more resemblance to osteoarthritis (OA) 2 . However, the underlying mechanism of this disease progression is not well understood.…”
Section: Figurementioning
confidence: 99%